Development of Historia Trivia Learning Media to Improve Digital Literacy and Cognitive Learning Outcomes in History of Grade XI Students at Pilangkenceng State High School - Sofyan Ariefullah; Parji Parji; Sudarmiani Sudarmiani (Universitas Islam Negeri Sumatera Utara, 2026)
This research focuses on the development of Historia Trivia as a learning medium and examines its feasibility and effectiveness in enhancing digital literacy skills and cognitive learning outcomes in history among eleventh-grade students at Pilangkenceng State Senior High School. The study employs a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through questionnaires administered to teachers and students, validation instruments completed by media and subject-matter experts, and cognitive tests and assignments in the form of pretests and posttests. The findings reveal that the Historia Trivia learning media is highly feasible, achieving a validation score of 90%, and has been shown to improve students’ digital literacy and learning outcomes significantly. Students’ average cognitive scores increased by 17.5 points, rising from 67.5 to 85. Additionally, scores on digital literacy assignments improved by 37.5 points, from 45 to 82.5. Overall, the study concludes that the developed learning media are both successful and effective in supporting students’ digital literacy development and comprehension of historical content.